Protection of Rohingya Refugees: Collective Responsibility of ASEAN Member States under International Law - Alejandro , Alejandro (PERFECT EDUCATION FAIRY, 2025)
The Rohingya refugee crisis has emerged as one of Southeast Asia’s most pressing humanitarian and legal challenges. Rooted in systemic persecution and statelessness in Myanmar, the plight of the Rohingya has led to large-scale forced displacement across the region. This article examines the legal obligations of ASEAN member states concerning refugee protection under international law, particularly the principle of non-refoulement, and evaluates ASEAN’s role as a regional organization in coordinating collective responsibility. Using a normative legal methodology, the study adopts statute, case, and conceptual approaches to analyze the gaps between international legal standards and ASEAN’s regional practices. Findings reveal that while most ASEAN states have not ratified the 1951 Refugee Convention and the 1967 Protocol, they remain bound by customary international law. ASEAN’s current response—largely humanitarian and short-term—falls short of establishing durable legal protection mechanisms. The article argues for the urgency of developing a regional refugee protection framework, modeled on the Comprehensive Plan of Action (CPA) for Vietnamese refugees in 1989, as a viable strategy to balance humanitarian imperatives with state sovereignty.